Essays in self-portraiture a comparison of technique in the self-portraits of Montaigne and Rembrandt - Small, Andrew (Renaissance and baroque, 1996)
By pairing specific self-portraits, the author compares Rembrandt and Montaigne in terms of courtiership and in terms of religious wisdom and ignorance. The book closes by showing how both artists used dissimilarity in their self-portraits. By selectively embracing and rejecting certain exemplars, Montaigne and Rembrandt constructed two of our most complete examples of the early modern self